Two new dragonflies (Odonata: Anisoptera) from the Miocene of Carinthia (Austria) - Schädel, Mario; Lechner, Thomas S. (Zootaxa, 2017)
Two new species of fossil dragonflies from the Middle Miocene fossil site Schaßbach (Carinthia, Austria) are described. The presence of Gomphaeschna carinthiae sp. nov. and Ictinogomphus hassleri sp. nov. in the fossil record of Central Europe confirms the scenario of a more widespread distribution of the represented genera in the Miocene in contrast to their Recent distribution.